Surface wave manipulation by plasmonic metasurface based on mode resonance - Baoshan Guo (Nature Portfolio, 2021)
Abstract We proposed a method to manipulate the surface waves with a deep subwavelength metasurface by applying resonators with interfering mode resonance. The simulation results demonstrate that a single deep subwavelength obstructed groove can effectively control the propagation of surface terahertz (THz) waves by a small step increase (< 1/20 λ) of the depth or a slight change of refractive index (Δn = 0.1). The surface waves transmitted and reflected by the single groove can be controlled periodically by increasing the groove depth or refractive index with a high efficiency owing to the mode resonance between surface spoof plasmonics modes and groove cavity modes. The generated circle resonance mode provides a new idea for the development of THz devices. Importantly, the transmitted or reflected intensity of the surface wave is also enhanced by the Mode resonance. It is a simple and effective method to operate surface THz waves and manufacture more compact integrated optical devices in deep subwavelength scale.